OPTIMIZATION OF WELDING PARAMETERS FOR DISSIMILAR MATERIALS WEAR PLATE HB500 AND AISI 318LN USING TAGUCHI METHOD - Marga Yogatama; Arif Wahjudi (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Welding dissimilar materials such as wear plate HB500 and duplex stainless steel AISI 318LN presents significant challenges due to the formation of brittle intermetallic phases, differences in thermal expansion, and residual stresses. This research aims to determine the optimal combination of welding parameters preheat temperature, electrode type, welding current, PWHT temperature, and PWHT holding time using the Taguchi L18 orthogonal array. Mechanical responses evaluated include tensile strength and impact toughness, which were combined using the Multi-Response Performance Index (MRPI). Experimental results indicate that PWHT temperature contributes most significantly to the combined mechanical response (44%), followed by electrode type (14%) and preheat temperature (12%). Welding current and PWHT time were statistically insignificant (p > 0.05). The optimal parameter combination determined through Taguchi analysis is electrode E2209, preheat 150°C, and PWHT 400°C. Confirmation tests produced an MRPI value of 0.833, which lies within the 95% confidence interval of predicted values (0.575–0.942). Thus, the Taguchi method demonstrated reliable predictive capability for optimizing welding parameters for dissimilar HB500–AISI 318LN joints.